Physiological and hormonal data of soccer during a Tough Match in Hot and Humid Environment - BAZABA KAYILOU, Jean-Michel; AHOUNOU AÏKPE, FIFAMIN JUDITH; Akakpo, B. Huguette; Kotin, Lucrèce M.; GBENOU, Djimon Joachim; DANSOU, HOUNDJOVI PIERRE (My University, 2021)
The present study aims was to evaluate the physiological and hormonal match parameters of elite soccer in a warm and humid environment. Hormonal parameters were evaluated before and after football match in a hot and humid environment. Physiological parameters were taken during the match. It is of heart rate, water loss and energy expenditure. The hormonal parameters were stress hormones and hydrominerals. The physiological data indicates a decrease in intensity of play during the match in a warm environment. A water loss more than 3% was noticed despite the amount of water consumed by soccer during the match. A decrease in blood cortisol levels was observed while catecholamines increased at the end of the match. Hydromineral hormones involved in physical exercise, indicated an increase in aldosterone and antidiuretic hormone values at the end of the match. The results show the importance to evaluate physiological and hormonal match data of footballers for hight performance.
Keywords: hot and humid environment - physiological hormonal – parameters